Composition and antifungal activity of Zhumeria majdae essential oil - Zahra Imani; Jinus Asgarpanah; Farshad Hashemi; Jamal Hashemi Hezaveh (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: Essential oils extracted from different plants are extensively used in perfume, beverage, and food industries and are reported to exhibit antimicrobial activities against a variety of fungi. Zhumeria majdae belonging to the Lamiaceae family is a rare and endemic medicinal plant species in Iran, with a strong and pleasant odor. The leaves of this plant have been used for many years as an antiseptic carminative agent for the treatment of stomachache (especially in infants) and dysmenorrhea. Materials and Methods: Gas chromatography/mass spectrometry (GC/MS) analysis was performed to determine the main constituents of the essential oil extracted from the aerial parts of Z. majdae. Also, the minimum inhibitory concentrations (MICs) were determined, using serial dilution method. Results: Based on the GC/MS analysis, 31 compounds representing 95.36% of the essential oil, extracted from the aerial parts of the plant, were identified, among which linalool (63.40%) and camphor (27.48%) were recognized as the major constituents. The total phenolic content was 42.74 GAE (mg)/DW (g). The hydro-distilled essential oil from the aerial part of the plant displayed potential antifungal activities against all the tested pathogenic fungal species (i.e., Candida albicans, Trichophyton mentagrophytes, Aspergillus flavus, Trichophyton rubrum, Microsporum canis, Microsporum gypseum, and Epidermophyton floccosum). Based on the inhibition zone (29 mm) and MIC value (0.015 l/ml), all the tested strains were sensitive to Z. majdae essential oil. Conclusion: The present results support the traditional and possible use of Z. majdae essential oil in food, pharmaceutical, and cosmetic industries.Background and Purpose: Essential oils extracted from different plants are extensively used in perfume, beverage, and food industries and are reported to exhibit antimicrobial activities against a variety of fungi. Zhumeria majdae belonging to the Lamiaceae family is a rare and endemic medicinal plant species in Iran, with a strong and pleasant odor. The leaves of this plant have been used for many years as an antiseptic carminative agent for the treatment of stomachache (especially in infants) and dysmenorrhea. Materials and Methods: Gas chromatography/mass spectrometry (GC/MS) analysis was performed to determine the main constituents of the essential oil extracted from the aerial parts of Z. majdae. Also, the minimum inhibitory concentrations (MICs) were determined, using serial dilution method. Results: Based on the GC/MS analysis, 31 compounds representing 95.36% of the essential oil, extracted from the aerial parts of the plant, were identified, among which linalool (63.40%) and camphor (27.48%) were recognized as the major constituents. The total phenolic content was 42.74 GAE (mg)/DW (g). The hydro-distilled essential oil from the aerial part of the plant displayed potential antifungal activities against all the tested pathogenic fungal species (i.e., Candida albicans, Trichophyton mentagrophytes, Aspergillus flavus, Trichophyton rubrum, Microsporum canis, Microsporum gypseum, and Epidermophyton floccosum). Based on the inhibition zone (29 mm) and MIC value (0.015 l/ml), all the tested strains were sensitive to Z. majdae essential oil. Conclusion: The present results support the traditional and possible use of Z. majdae essential oil in food, pharmaceutical, and cosmetic industries.